HEMISECTION AS A CONSERVATIVE TREATMENT OPTION OF BIFURCATION PERFORATION: CASE REPORT - Regia Aristiyanto; Aqilla Tiara Kartikaningtyas (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Hemisection is sectioning and removal of one root and its crown portion on multi-rooted teeth. Hemisection denotes a conservative treatment option for large bifurcation perforation, loss of periodontal attachment and was performed to maintain the original teeth structure. This case report aims is to present the management of hemisection of a mandibular first molar with crown rehabilitation. Case and Management: A 16-year-old male complained of pain while biting on his right lower teeth. Clinical examination showed deep caries on the occlusal surface, the tooth has a positive response on percussion and palpation tests. The mobility test was positive on the mesial root and crown. Based on periapical radiographic examination, there was a radiolucent feature extended to the bifurcation area. The diagnosis was pulp necrosis and symptomatic apical periodontitis accompanied by bifurcation perforation. Root canal treatment and hemisection were performed to remove infected tissue, and the remaining part of the teeth was restored with a porcelain-supported fixed prosthesis. Conclusion: Hemisection can be a suitable conservative treatment for teeth with extensive damage and has a good long-term prognosis.